The development of a response surface model for the determination of infinite dilution partial molar volumes and excess volumes from dilute multi-component data alone. Implications for the characterization of non-isolatable solutes in complex homogeneous reactive systems - Tjahjono, M. (2014)
10.1016/j.ces.2004.12.044